Congenital Blindness and Psychosis: A Literature Review - Retno Tharra Handayani (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2021)
Low vision has been declared by the World Health Organization (WHO) to be one of the major ophthalmologic problems requiring global attention. Low-vision patients experience a reduced vision-related quality of life due to impaired visual function. However, this condition that interfere their daily life could also make a significant effect on their mental health. Therefore, the final goal of low-vision rehabilitation is to improve the daily quality of life. However, the absence of vision at birth appears to protect against psychosis, whereas later-life visual loss appears to predispose to the development of psychotic symptoms. Thus, our purpose in this literature review is to learn how the onset of visual loss may affect patient's mental health.